Al-Rajhi Bank: setting an ummatic vision of international management - Khaliq, Ahmad; Mustafa Omar, Mohammed (Management Centre, IIUM, 2011)
Al-Rajhi Bank, from Saudi Arabia, is making its presence felt in the Malaysian market with the establishments of many branches throughout the country, providing its products and services to the competitive Islamic banking segments in the local market. It has proven itself to be effective and efficient in its services while declaring lucrative profits by the year end - 2011, that is an increase of 26%. Carefully monitored by its own Shariah Board it has not only inculcated Islamic values in its products and services but has also stressed on adherence to the Islamic code of conduct by the members of its management teams, the people behind its many successes and accomplishments. The bank is professionally managed according to its vision, mission and values.